2014
DOI: 10.1002/fsn3.149
|View full text |Cite
|
Sign up to set email alerts
|

Rehydration characteristics of dehydrated West African pepper (Piper guineense) leaves

Abstract: The rehydration characteristics of dehydrated West African pepper leaves were investigated at hydration temperatures of 28, 60, 70, and 80°C. Four treatments were given to the leaves: blanched and sun dried, unblanched and sun dried, blanched and shade dried, and unblanched and shade dried. The hydration process of the dehydrated leaves was adequately described by the Peleg's equation. As the hydration temperature increased from 28 to 70°C, there was a significant decrease in the Peleg's constant K1, while for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…The first method given in Equation 4 as RR1 is commonly used as a simple indicator of the progress of the rehydration process, as the weight (g) of the rehydrated material divided by the original weight (g) of the dried material (Fathima et al, 2001;Gornicki, Kaleta, Winiczenko, Chojnacka, & Janaszek, 2013;Jokic et al, 2009;Maskan, 2001;Okpala & Ekechi, 2014). The rate of change in moisture content was calculated as the change in moisture content as a function of average time (s) and expressed in g H 2 O/g DM/s.…”
Section: Rehydration Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The first method given in Equation 4 as RR1 is commonly used as a simple indicator of the progress of the rehydration process, as the weight (g) of the rehydrated material divided by the original weight (g) of the dried material (Fathima et al, 2001;Gornicki, Kaleta, Winiczenko, Chojnacka, & Janaszek, 2013;Jokic et al, 2009;Maskan, 2001;Okpala & Ekechi, 2014). The rate of change in moisture content was calculated as the change in moisture content as a function of average time (s) and expressed in g H 2 O/g DM/s.…”
Section: Rehydration Data Analysismentioning
confidence: 99%
“…To facilitate comparison of the results of this study with those of previously reported studies, a rehydration ratio (RR) was calculated using two methods seen in rehydration studies. The first method given in Equation 4 as RR1 is commonly used as a simple indicator of the progress of the rehydration process, as the weight (g) of the rehydrated material divided by the original weight (g) of the dried material (Fathima et al, 2001;Gornicki, Kaleta, Winiczenko, Chojnacka, & Janaszek, 2013;Jokic et al, 2009;Maskan, 2001;Okpala & Ekechi, 2014). The second method given in Equation 5 is based upon the ratio between the absorbed water (g) divided by the weight (g) of dry matter in the dried material (Balasubramanian et al, 2011;Doymaz, 2014):…”
Section: Rehydration Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The rehydration capacity is affected by the various factors such as the drying conditions, product type, temperature degree, ratio of the rehydration water to that in the dried product. Therefore, when stating the quantitative value regarding the rehydration capability of a product, it is necessary to identify in detail the methods and conditions under which the value was determined (Okpala & Ekechi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Rehidrasyon düzeyi, kullanılış amacına göre değişmektedir. Orta nemli gıda elde etme de bu amaçlardan birisidir [12]. Kurutulmuş havuç dilimlerinin kurutma kinetiği üzerine literatürde birçok araştırma mevcut olup rehidrasyon kinetiği ile ilgili ise herhangi bir çalışma mevcut değildir.…”
Section: Gi̇ri̇ş (Introduction)unclassified